The Relation Between Physical Activity and Mental Health in Health Faculty and Non-Health Faculty Students - Laila Safariana; Tri Laksono; Muh. Irfan (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: College students are individuals who study at university. Academic workload, cumulative grade point average (GPA) competition, parents' expectations, living away from home, and the environment trigger the mental problems on students. Students often engage in physical activities during coursework, influencing their non-academic routines. Faculty differences lead to varying academic loads and lifestyles, affecting mental health management and physical activity levels. Objective: Study aimed to know the physical activity and mental health of the Health Sciences (FIKES) and Non-Health Sciences (Non-FIKES) Faculties students. Methods: This research applied a quantitative method, with an observational analytic study design. The sampling was performed by purposive sampling technique, with the total of 520 respondents. The research instruments used were the International Physical Questionnaire-Short Form (IPAQ-SF) and Depression, Anxiety, Stress, Scale 21 (DASS-21). The data analysis was conducted by a univariate analysis; normality test; bivariate analysis used Rank-Spearman test; and Mann-Whitney test. Result: Rank-Spearman correlation showed that there was a significant relation between physical activity and depression, anxiety, and stress (r=-0.365, p=0.000, r=-0.294, p=0.000, r=- 0.270, p=0.000). The Mann-Whitney test on physical activity, depression, anxiety, and stress on FIKES and Non-Fikes Students had a significant difference (p=0.000, p=0.000, p=0.000, p=0.000). Conclusion: There is a significant relation between physical activity and mental health for FIKES and Non-FIKES Students, and there is a significant difference between physical activity and mental health for FIKES and Non-FIKES Students.